2007
DOI: 10.1093/carcin/bgl112
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and caffeine sodium benzoate have a sunscreen effect, enhance UVB-induced apoptosis, and inhibit UVB-induced skin carcinogenesis in SKH-1 mice

Abstract: Topical application of caffeine sodium benzoate (caffeine-SB) immediately after UVB irradiation of SKH-1 mice enhanced UVB-induced apoptosis by a 2- to 3-fold greater extent than occurred after the topical application of an equimolar amount of caffeine. Although topical application of caffeine-SB or caffeine enhanced UVB-induced apoptosis, both substances were inactive on non-UVB-treated normal skin. Topical application of caffeine-SB or caffeine (each has UVB absorption properties) 0.5 h before irradiation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 26 publications
(29 reference statements)
1
62
0
4
Order By: Relevance
“…In recent studies, we identified caffeine sodium benzoate as a complex of caffeine and sodium benzoate that is more active than caffeine at enhancing UVB-induced apoptosis (27). Our hypothesis predicts that administration of caffeine or caffeine sodium benzoate will inhibit UVB-induced activation of the ATR/Chk1 pathway by inhibiting the phosphorylation of Chk1 at Ser 345 , thereby leading to increased cyclin B1, premature chromatin condensation, premature mitosis, and cell death in DNA-damaged cells (see Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In recent studies, we identified caffeine sodium benzoate as a complex of caffeine and sodium benzoate that is more active than caffeine at enhancing UVB-induced apoptosis (27). Our hypothesis predicts that administration of caffeine or caffeine sodium benzoate will inhibit UVB-induced activation of the ATR/Chk1 pathway by inhibiting the phosphorylation of Chk1 at Ser 345 , thereby leading to increased cyclin B1, premature chromatin condensation, premature mitosis, and cell death in DNA-damaged cells (see Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Studies from our laboratory showed that administration of caffeine or caffeine sodium benzoate has sunscreen activity, increases the elimination of DNA-damaged cells by apoptosis, and inhibits UVB-induced carcinogenesis in SKH-1 mice (3,4,7,8,27,42). Topical applications of caffeine or caffeine sodium benzoate to UVBpretreated high-risk mice inhibited carcinogenesis in the absence of further UVB treatment (4,27,42), and administration of caffeine also enhanced apoptosis in the tumors (42). The results of these studies suggest that caffeine and caffeine sodium benzoate may be mechanistically novel agents for inhibiting sunlight-induced skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Along with its role as an antioxidant (17), recent studies have shown additional anticarcinogenic properties of caffeine, that include antimetastatic effects (30), the ability to inhibit cell proliferation (31), and enhance apoptosis (32). With respect to mammary tumorigenesis, one group reported that chronic caffeine exposure prior to the appearance of the tumor was associated with a significant reduction in tumor burden and metastasis in a transgenic mouse model (33).…”
Section: Discussionmentioning
confidence: 99%
“…This active shows potential anticancer effects upon oral and topical administration, and is able to protect the skin from ultraviolet (UV) light induced skin cancer (Dias et al, 1999;Koo et al, 2007;Lu et al, 2007;Roure et al, 2011;Gee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%